Long-Run Effects of Trade Liberalization on Local Labor Markets : Evidence from South Africa - Bastos, Paulo; Santos, Nicolas (World Bank, Washington, DC, 2021)
This paper uses municipal-level data from South Africa for the period 1996–2011 to estimate the medium to long-run effects of trade liberalization on local labor markets. It finds that local labor markets that were more exposed to tariff cuts tended to experience slower growth in employment and income per capita than less exposed regions. The longer-term effects of trade liberalization on regional earnings are stronger than the medium-term effects, and tend to be more pronounced among municipalities that included the former homelands.